Building Climate Resilience in Rainfed Landscapes Needs More Than Good Will - Barron, Jennie; Skyllerstedt, Susanne; Giordano, Meredith; Adimassu, Zenebe (Frontiers in Climate, 2021)
Rainfed smallholder farming is particularly vulnerable to climate change, which can greatly exacerbate existing poverty and livelihood challenges. Understanding the complexity of the systems that connect the environment, society and people can help us to reduce this vulnerability and increase the resilience of communities and households to climate perturbations. In recent years, resilience theory has proven a useful approach for exploring the complexity of development challenges. As a result, there has been an increase in the development of tools and frameworks for assessing resilience. Despite this increased focus, there is no consistent use of the resilience concept in development practice and little evidence as to the benefits of using the tools. This paper aims to bridge theory and practice by coupling research on resilience with its application in the international development field. We explore the hypothesis how rural livelihoods build resilience towards increased climatic variability in degraded agro-ecological landscapes? We present a resilience framework with indicators to assess the extent of community resilience to climate change through improved local agricultural production and natural resources management. Primary and secondary landscape and community data, together with development of participatory watershed action plans were used to populate 16 indicators in a resilience framework baseline for the two rainfed dominated watersheds in Ethiopia and Ghana respectively. Given community awareness of the challenges related to the watershed, local agriculture and extreme weather, the communities were willing to develop action plans to improve management of natural resources and build climate resilience. Nevertheless, our analysis of the watershed action plans revealed that strengthening resilience through local action alone, would likely not be sufficient to meet all climate -livelihood challenges identified. To address severity and recurrence of climate change related disturbances, such as droughts, floods and disease the capacity to improve resilience will depend on external factors, for example new knowledge, infrastructure and social security mechanisms. We conclude there are also challenges in the use of resilience framework for development and climate-action related to rural poverty affected and degraded livelihood systems. Populating complex social–environmental systems will need further development, to understand progress in resilience building under changing climate.